2021
DOI: 10.1021/acsomega.1c02734
|View full text |Cite
|
Sign up to set email alerts
|

Functional Group Characteristics and Pyrolysis/Combustion Performance of Karamay OS Based on FT-IR and TG–DTG Analyses

Abstract: Proximate analysis, ultimate analysis, Fourier-transform infrared spectroscopy (FT-IR), and thermogravimetry−differential thermal analysis characterization were carried out on oily sludge (OS) samples OS1−OS5, from Karamay, Xinjiang, China. The Coast− Redfern model (CRm) was used to simulate the pyrolysis and combustion kinetics of oily samples. The results showed that the peak area percentage of benzene ring trisubstitution of OS5, in the range of 700−900 cm −1 , is close to 75%, corresponding to its high vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…More researchers have used it. 26−28 Mo et al 29 studied the combustion performance for five kinds of oily sludge in Karamay by Fourier transform infrared (FTIR) and thermogravimetry-differential thermal analysis (TG-DTG) analyses, and found that the combustion performance was related to the volatile content. However, many studies 30−32 on pyrolysis/combustion characteristics focused on the combustion part, but there are a few studies on the calculation of the pyrolysis index.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More researchers have used it. 26−28 Mo et al 29 studied the combustion performance for five kinds of oily sludge in Karamay by Fourier transform infrared (FTIR) and thermogravimetry-differential thermal analysis (TG-DTG) analyses, and found that the combustion performance was related to the volatile content. However, many studies 30−32 on pyrolysis/combustion characteristics focused on the combustion part, but there are a few studies on the calculation of the pyrolysis index.…”
Section: Introductionmentioning
confidence: 99%
“…The Coats–Redfern model (CRm) is a commonly used approximation formula, and it is one of the well-known approximate formulas according to previous studies. , Although its accuracy needs to be improved, CRm is simple to linearize the kinetic equation. More researchers have used it. Mo et al studied the combustion performance for five kinds of oily sludge in Karamay by Fourier transform infrared (FTIR) and thermogravimetry-differential thermal analysis (TG-DTG) analyses, and found that the combustion performance was related to the volatile content. However, many studies on pyrolysis/combustion characteristics focused on the combustion part, but there are a few studies on the calculation of the pyrolysis index.…”
Section: Introductionmentioning
confidence: 99%